Physical Fitness and Health-related Quality of Life in Patients with Colorectal Cancer - Soares-Miranda, Luisa; Lucia, Alejandro; Silva, Marco; Peixoto, Armando; Ramalho, Rosa; da Silva, Pedro Correia; Mota, Jorge; Macedo, Guilherme; Abreu, Sandra (International Journal of Sports Medicine, 2021)
Colorectal cancer is now a frequently treatable illness for most and a chronic disease for many. The number of people living with a diagnosis of colorectal cancer is thus expected to rise. Yet even after successful treatment, colorectal cancer survivors, mostly the elderly, frequently experience health problems and impaired health-related quality of life. We investigated the cross-sectional association between physical fitness, measured with the 6-min walk test, 30-second chair-stand test, and isometric handgrip strength, as well as health-related quality of life, in a cohort of colorectal cancer patients (n=71, mean [SD] age 67±10 years, 63% men; 35, 39 and 25% in stages I, II and III, respectively). Greater performance in the 6-minute walk test and 30-second chair-stand test was associated with higher levels of global health status (p<0.001, p=0.001 respectively), higher functioning (p<0.001) and lower levels of symptomatology (p<0.001; pain and fatigue). Additionally, greater 6-min walk test performance was associated with a better cognitive function (p=0.005). Our results suggest that greater aerobic fitness and lower-extremity muscle strength are cross-sectionally associated with higher levels of global health status, higher functioning and lower levels of symptomatology such as pain and fatigue in colorectal cancer patients.
Keywords: cancer survivors; fitness; 6-min walk test; quality of life